Laser interstitial thermal therapy in the management of brain metastasis and radiation necrosis after radiosurgery: An overview. (1st February 2016) - Sharma, Mayur; Balasubramanian, Suresh; Silva, Danilo; Barnett, Gene H.; Mohammadi, Alireza M.
ABSTRACT: With advances in stereotactic and neuroimaging techniques, various minimally invasive image-guided techniques have gained widespread acceptance in the field of neuro-oncology. Laser interstitial thermal therapy (LITT) is an image-guided technique that involves generation of high temperatures using a laser fiber, to ablate pathological tissue. Radiation necrosis (RN) and radiosurgery resistant brain metastasis often pose significant challenges to the treating physicians. In the last two decades, various studies have documented the efficacy of LITT in managing radiosurgery resistant metastases, radiation necrosis, surgically inaccessible malignant gliomas and ablation of epileptogenic foci. The aim of this paper is to summarize the current literature on the efficacy of LITT in patients with radiation necrosis and brain metastasis. We have also touched upon the physical properties of currently available LITT systems and the mechanism of action of laser therapy including histopathological changes.